1989
DOI: 10.1016/0024-3795(89)90580-6
|View full text |Cite
|
Sign up to set email alerts
|

Majorization, doubly stochastic matrices, and comparison of eigenvalues

Abstract: Motivated by reachability questions in coherently controlled open quantum systems coupled to a thermal bath, as well as recent progress in the field of thermo-/vector-dmajorization [vom Ende and Dirr (2019)] we generalize classical majorization from unital quantum channels to channels with an arbitrary fixed point D of full rank. Such channels preserve some Gibbs-state and thus play an important role in the resource theory of quantum thermodynamics, in particular in Thermo-Majorization.Based on this we investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
244
0
5

Year Published

1993
1993
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 281 publications
(250 citation statements)
references
References 50 publications
1
244
0
5
Order By: Relevance
“…For any x D .x 1 ; x 2 ; :::; x m / 2 S m 1 , we define x # D .x OE1 ; x OE2 ; :::; x OEm / where x OE1 x OE2 ::: x OEm -nonincreasing rearrangement x. Recall [11,14] that for two elements x; y of the simplex S m 1 the element x is majorized by y and written x y ( or y x) if the following condition holds…”
Section: Preliminariesmentioning
confidence: 99%
“…For any x D .x 1 ; x 2 ; :::; x m / 2 S m 1 , we define x # D .x OE1 ; x OE2 ; :::; x OEm / where x OE1 x OE2 ::: x OEm -nonincreasing rearrangement x. Recall [11,14] that for two elements x; y of the simplex S m 1 the element x is majorized by y and written x y ( or y x) if the following condition holds…”
Section: Preliminariesmentioning
confidence: 99%
“…If M h = {m ∈ M | m = m * }, we recall that the spectral order ( [1]; see also [2]) on M h is defined by a ≺ b if the spectral projections satisfy…”
Section: 2mentioning
confidence: 99%
“…However, we cannot say that all QSOs are of Volterra-type, and the non-Volterra dynamics of QSO are still open. Basic properties of majorization and doubly stochastic matrices have been studied by Ando [14]. The limit behaviour of trajectories of QSOs was completely studied on 1D simplex by Lyubich et al [15], where it was shown that the limit of any initial values is a finite set.…”
Section: Introductionmentioning
confidence: 99%